VD_FINDINFO Jug / 2024 / 285 vom 21. November 2023 - VD Tribunal cantonal (2023)
LÉSION CORPORELLE SIMPLE, VOIES DE FAIT, MENACEDROIT PÉNAL, INJURE, CONTRAINTEDROIT PÉNAL, CONTRAINTE SEXUELLE, VIOL | 123 ch. 1 CP, 123 ch. 2 al. 6 CP, 126 al. 1 CP, 126 al. 2 CP, 177 al. 1 CP, 180 al. 1 CP, 180 al. 2 let. b CP, 181 CP, 189 al. 1 CP, 190 al. 1 CP, 19a ch. 1 LStup, 115 al. 1 let. b LEI